(untitled) (Journal of Applied Learning and Teaching, 2025)
Globally, generated AI tools have significantly changed the operations of higher education. This paper contests the claim that academics in the context of this study were exposed to and capacitated with AI literacy, tools and technological skills. The assumption is that they will successfully integrate AI technologies in humanising pedagogy for online learning spaces. This narrative-based research argues, from an AI-humanising pedagogical framework (AIHP), to explore multiple cases of academics integrating AI technologies in humanising pedagogical spaces. Findings reported that AI-generated tools promoted personalised learning, fostering empathy through realistic simulations, generating specific learning content to meet students’ needs, and facilitating collaborative learning. Thus, the proposed AI-humanising pedagogical framework provided an alignment in support of dimensions from the narrative-based inquiry depicted in three cases in the study. Higher education institutions must develop institutional AI policies and guidelines for ethical practices, transparency, accountability, and inclusivity in developing and deploying AI.